Systematic review of interventions for the prevention and treatment of postoperative urinary retention. Issue 1 (19th November 2018) - Jackson, J.; Davies, P.; Leggett, N.; Nugawela, M. D.; Scott, L. J.; Leach, V.; Richards, A.; Blacker, A.; Abrams, P.; Sharma, J.; Donovan, J.; Whiting, P.
Abstract : Background: Postoperative urinary retention (PO‐UR) is an acute and painful inability to void after surgery that can lead to complications and delayed hospital discharge. Standard treatment with a urinary catheter is associated with a risk of infection and can be distressing, undignified and uncomfortable. This systematic review aimed to identify effective interventions for the prevention and treatment of PO‐UR that might be alternatives to urinary catheterization. Methods: Electronic databases were searched from inception to September 2017. Randomized trials of interventions for the prevention or treatment of PO‐UR were eligible for inclusion. Studies were assessed for risk of bias using the Cochrane (2.0) tool. Two reviewers were involved at all review stages. Where possible, data were pooled using random‐effects meta‐analysis. The overall quality of the body of evidence was rated using the GRADE approach. Results: Some 48 studies involving 5644 participants were included. Most interventions were pharmacological strategies to prevent PO‐UR. Based on GRADE, there was high‐certainty evidence to support replacing morphine in a regional anaesthetic regimen, using alpha‐blockers (number needed to treat to prevent one case of PO‐UR (NNT) 5, 95 per cent c.i. 5 to 7), the antispasmodic drug drotaverine (NNT 9, 7 to 30) and early postoperative mobilization (NNT 5, 4 to 8) for prevention, and employing hot packs or gauze soaked in warm water for treatment (NNT 2, 2 to 4). Very few studies reported on secondary outcomes of pain, incidence of urinary tract infection or duration of hospital stay. Conclusion: Promising interventions exist for PO‐UR, but they need to be evaluated in randomized trials investigating comparative clinical and cost effectiveness, and acceptability to patients. Abstract : Post‐operative urinary retention (PO‐UR) is an acute and painful inability to void following surgery which can lead to complications and delayed hospital discharge. This systematic review aimed to identify effective interventions for the prevention and treatment of PO‐UR. Promising interventions exist but need to be evaluated in randomized trials investigating their comparative clinical and cost effectiveness and acceptability to patients. Too many poor quality trials